Pomp and circumstance : a novel - Stewart, Fred Mustard (New York : Dutton, 1991)
"The great manor houses of mid-Victorian England. The glittering Paris of the second empire. The vast plantations of the antebellum south. The violent battlefields of the civil war. The grandeur and danger of the British Raj in India. All come together in Fred Mustard Stewart's most sweeping and spellbinding triumph--a saga of star crossed love and divided destinies that marks a new high in rich romance and vivid historical adventure."--Cover.
National College of Business and Arts
Keywords: United States -- History -- Civil War, 1861-1865 -- Fiction; Historical fiction